Aggravate or Mitigate? How Cost Analysis Associated into Risk Management Process - Winda Nur Cahyo; Eky Fasich Trialopa; Hari Purnomo (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
In most researches in the area of risk management, the result stops at proposing the mitigation strategies. The number of researches on associating cost analysis into the risk management process is very limited. This paper proposes a practical process on how cost analysis can be associated into the risk management process especially in the area of manufacturing. The process of the risk management is conducted as usual, started by selecting the potential risk and finding the major causes. Then, a risk map and its rubric of risk likelihood and severity are developed, and the major causes are plotted into it to select the priority of the major causes and the proposed mitigation strategy is developed. Then, the poposed strategy is compared with the current strategy based on the cost generated using the developed equation. The result shows the proposed mitigation strategy is selected because it saves approximately IDR 2 million per order. It indicates that cost analysis can be successfully associated into the risk mitigation process and generates a comprehensive recommendation to the decision maker.